Management level of Intellectual Capital in the Palestinian Universities from the Perspective of Faculty Members in Relationship to the Aspects of Excellence - Mahmoud A.R. Assaf (University of Science and Technology, Yemen, 2017)
The study aimed to identify the degree of assessment given by faculty members of the Palestinian universities about their efforts in managing the intellectual capital, and to identify the aspects of excellence mostly preferred by them and the relationship between these aspects. To achieve the objectives of the study, the researcher followed the descriptive method by applying two questionnaires: the first consisting of (37) items; and the second comprising (28) items distributed to (4) areas. The sample consisted of (229) faculty members from these universities: (Al-Azhar, the Islamic university and al-Aqsa). They were selected using the random stratified method. The results were as follows: The respondents' total degree of assessment of the efforts exerted by the universities in intellectual capital was at the rate of (63.8%), which is a medium degree. The area of (management of relations) came in first place at a rate of (71.2%) with a large degree. The 'management of intellectual and organizational assets' was given the last rank with a medium degree and the rate of (56.80%) The aspect of excellence that was given the first rank by the respondents was the (development of faculty members and teaching) at the rate of (65.2 % ), and with a medium degree. The least trend is (supporting talent and creativity ) which came in the last rank, with a medium degree and a rate of (59.4%). There was a statistically significant correlation of (α≤0.05) between the degree of respondents' assessment of university efforts in managing intellectual capital and their assessment of the aspects of excellence, recording a correlation coefficient of (0.737 ).  Keywords: Aspects of excellence, Intellectual capital, Efforts of Palestinian Universities.